2016
DOI: 10.1155/2016/4902714
|View full text |Cite
|
Sign up to set email alerts
|

A Systematised Review of Primary School Whole Class Child Obesity Interventions: Effectiveness, Characteristics, and Strategies

Abstract: Background. A systematised review was conducted to examine the effectiveness of school-based interventions that focus on changing dietary intake and physical activity levels to reduce childhood obesity. Methods. Multiple databases were searched for randomised and nonrandomised interventions from 2007 to 2016 in full-time elementary schools, which were delivered to the whole class, included dietary and physical activity components, involved both sexes, were written in English, and used body mass index (BMI) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 56 publications
2
35
0
4
Order By: Relevance
“…These findings highlight the paucity of high-quality, theory based interventions to mitigate the effects of overweight and obesity, and energy-related behaviours among African children. A considerable body of evidence suggests that multicomponent school-based interventions that target PA, dietary behaviours, sedentary behaviours, and the environments are more likely to be effective in children and adolescents compared with single component interventions [15][16][17][18]34]. Given the multi-faceted nature of overweight and obesity, it is not surprising that programmes that target individual behaviours and the obesogenic environments simultaneously are promising.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the paucity of high-quality, theory based interventions to mitigate the effects of overweight and obesity, and energy-related behaviours among African children. A considerable body of evidence suggests that multicomponent school-based interventions that target PA, dietary behaviours, sedentary behaviours, and the environments are more likely to be effective in children and adolescents compared with single component interventions [15][16][17][18]34]. Given the multi-faceted nature of overweight and obesity, it is not surprising that programmes that target individual behaviours and the obesogenic environments simultaneously are promising.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de que diversas revisiones sistemáticas muestran que las intervenciones basadas en escuelas para prevenir la enfermedad son efectivas (6)(7)(8) , en nuestro país solo encontramos un estudio controlado que evaluó la efectividad de este tipo de intervenciones. A diferencia de nuestros resultados, Gago et al encontraron efectos al año de implementar una intervención multisectorial en educación alimentaria-nutricional en la prevención del sobrepeso u obesidad en escolares de IE de un distrito de Lima (27) .…”
Section: Discussionunclassified
“…La escuela es un escenario adecuado para realizar intervenciones contra la obesidad, porque es donde los escolares pasan gran parte de su tiempo, toman algunas de las comidas y son educados de manera natural sobre estilos de vida saludables; además, junto al ámbito familiar son los espacios educativos que más influyen en la adquisición de hábitos alimentarios y estilos de vida saludable (7,2) .…”
Section: Introductionunclassified
“…Five systematic reviews included both randomized controlled trials (RCTs) and studies that were not randomized or did not include a control and two reviews included RCTs only. Four systematic reviews synthesized results using meta‐analysis, and four undertook a systematic search but described the findings using narrative review . No values were reported in the papers using narrative review; therefore, these are considered in terms of reported significance of effect.…”
Section: Characteristics Of Selected Reviewsmentioning
confidence: 99%
“…McGoey et al (2016) found that 68.8% of studies reported statistically significant increases for studies of interventions that focused solely on improving physical activity compared with controls (no values reported). Further, three reviews of studies focusing on interventions that included increasing physical activity as part of multistrategy interventions (including a focus on diet and other lifestyle behaviours) found positive effects for increasing children's participation in physical activity …”
Section: What Are the Most Effective Intervention Components?mentioning
confidence: 99%